Applicability of Some General Prediction Correlations of Flow Boiling to a Few Pure Substances - Chen Dongsheng; Shi Yumei; Gao Zhiqian (Zhileng xuebao)
Flow boiling heat transfer is an important heat transfer method, and many prediction correlations for flow boiling heat transfer have been proposed for a variety of substances. But as the correlations are all empirical or semi-empirical, the accuracy of predicted results would be very different when applying them on different substances or in different working condition. To evaluate the applicability of the present flow boiling prediction correlations for pure substances, eight general predictive correlations are chosen and the prediction results of them are compared with the experimental data from some open literatures for R134a, CO2, liquid nitrogen. The results show that Lazarck(1982) correlation、Kew and Cornwell(1997) correlation have good prediction accuracy for the three substances, and Gungor and Winterton(1987) correlation may be more applicable for CO2，Liu and Winterton(1991) correlation has good prediction accuracy for R134a. But the others all fail to predict heat transfer coefficient（HTC）accurately for the three substances. In addition, the eight correlations have not enough accuracy to predict HTC of flow boiling for liquid nitrogen.